Non-skid composition, non-skid layer, and non-skid laminate
Patent Information
- Application Number
- JP2025207371
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-11-27
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-11-27
AI Technical Summary
【0018】 本発明によれば、高いノンスキッド性を有しながら、極めて高い耐衝撃性に優れるノンスキッド層を形成することができる。従って、該ノンスキッド層は、車両甲板や飛行甲板、特に飛行甲板に好適に用いることができ、艦船のデッキにより好適に用いることができる。
Smart Images

Figure 0007933998000008 
Figure 0007933998000001 
Figure 0007933998000002
Abstract
Description
[Technical Field]
[0001] This invention relates to a non-skid composition, a non-skid layer, and a non-skid laminate. [Background technology]
[0002] Non-skid layers with a high coefficient of static friction on the surface are used in various places such as concrete floors, stairs, and poolside areas to reduce the risk of slipping, sliding, and falling.
[0003] Among the various locations mentioned above, the vehicle deck surface of car carriers and the flight deck surface of ships used for aircraft operations (including helicopters) require particularly high levels of non-skid properties (anti-slip properties).
[0004] As a composition that can form surfaces requiring particularly high non-skid properties (anti-slip properties), for example, Patent Documents 1 and 2 describe the use of epoxy resin-based compositions. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2000-178502 [Patent Document 2] Special Publication No. 2010-515787 [Overview of the project] [Problems that the invention aims to solve]
[0006] The layers formed on the surface of the vehicle deck and flight deck require high non-skid properties, as well as resistance to impacts from vehicles and aircraft (impact resistance). In particular, the flight deck requires extremely high impact resistance to withstand the takeoffs and landings of helicopters and fighter jets. However, it has been found that there is room for improvement in terms of impact resistance when using conventional compositions.
[0007] The present invention has been made in view of the above circumstances, and an object thereof is to provide a non-skid composition capable of forming a non-skid layer that has high non-skid properties and is extremely excellent in impact resistance. [MEANS FOR SOLVING THE PROBLEM]
[0008] As a result of extensive and intensive studies on methods for solving the above problems, the present inventors have found that the above problems can be solved according to the following configuration examples, and have completed the present invention. Configuration examples of the present invention are as follows.
[0009] [1] A non-skid composition comprising a first agent containing an epoxy resin (AN) and a second agent containing an amine compound (BN), wherein the epoxy equivalent based on the solid content of all epoxy compounds contained in the first agent is 450 or less, the amine compound (BN) contains an alicyclic amine compound, and the non-skid layer formed therefrom has a surface static friction coefficient of 0.80 or more.
[0010] [2] The non-skid composition according to [1], which contains an aggregate having an average particle size of 0.1 to 3.0 mm, and the content of the aggregate is 15% by mass or more based on 100% by mass of the solid content of the first agent.
[0011] [3] The non-skid composition according to [2], wherein the aggregate contains at least one selected from aluminum oxide and aluminum powder.
[0012] [4] The non-skid composition according to any one of [1] to [3], wherein the pigment volume concentration (PVC N ) of the particulate solid is 40.0% or more.
[0013] [5] A non-skid layer formed from the non-skid composition according to any one of [1] to [4].
[0014] [6] A non-skid laminate having a primer layer and the non-skid layer described in [5].
[0015] [7] Volume concentration of particulate solids in the primer layer (PVC P The non-skid laminate described in [6], wherein ) is 32.0% or less. [8] The PVC P and the volume concentration of particulate solids in the non-skid layer (PVC N ) is the difference with PVC N -PVC P A non-skid laminate according to [6] or [7], wherein the content is 19.0% or more.
[0016] [9] The non-skid laminate according to any one of [6] to [8], wherein the primer layer is a layer formed from a primer composition containing a main component comprising an epoxy resin (AP) and a curing agent comprising an amine compound (BP).
[0017]
[10] A non-skid laminate as described in any of [6] to [9], for use in ships. [Effects of the Invention]
[0018] According to the present invention, it is possible to form a non-skid layer that has high non-skid properties while also having extremely high impact resistance. Therefore, this non-skid layer can be suitably used on vehicle decks and flight decks, and especially on flight decks, and is more suitably used on the decks of ships. [Brief explanation of the drawing]
[0019] [Figure 1] Figure 1 is a schematic diagram showing the sequence of dropping the tap onto the non-skid layer in the impact resistance test in the embodiment described below. [Modes for carrying out the invention]
[0020] Non-skid composition The non-skid composition according to the present invention (hereinafter also referred to as "the present composition") is a composition for forming a non-skid layer having a surface static friction coefficient of 0.80 or more, which contains a first agent containing an epoxy resin (AN) and a second agent containing an amine compound (BN), wherein the epoxy equivalent of the solid content of all epoxy compounds contained in the first agent is 450 or less, and the amine compound (BN) contains an alicyclic amine compound.
[0021] The present composition is not particularly limited as long as it is a multi-component composition including the first agent and the second agent, and may be a two-component composition composed of the first agent and the second agent, or depending on the components used, may be a three or more-component composition including a third agent other than the first agent and the second agent, but from the viewpoint of ease of forming the non-skid layer and the like, a two-component composition is preferred. Agents such as the first agent, the second agent and the third agent (hereinafter collectively referred to as "n-th agent") are usually stored, preserved, transported and the like in separate containers, and are used after being mixed into a composition when the multi-component composition is used (e.g., immediately before coating).
[0022] Volume concentration of particulate solids in the present composition (PVC N ) is preferably 40.0% or more, more preferably 45% or more, still more preferably 50% or more, particularly preferably 52% or more, and is preferably 70% or less, more preferably 65% or less. PVC N falls within the above range, it tends to be possible to easily form a non-skid layer (non-skid laminate) excellent in non-skid properties, impact resistance and abrasion resistance. Note that PVC N is synonymous with the volume concentration of particulate solids in the non-skid layer.
[0023] In the present specification, PVC refers to the total volume concentration of particulate solids in the composition relative to the volume of non-volatile content of the composition, and specifically can be determined by the following formula (1). The particulate solid in the numerator of the following formula refers to solid particles including the following pigments, aggregates, thixotropic agents and the like. PVC (%) = Total volume of particulate solids in the composition × 100 / Volume of non-volatile content in the composition ... (1)
[0024] The volume of the non-volatile content of a composition can be calculated from the mass and true density of the non-volatile content of the composition. The mass and true density of the non-volatile content of the composition may be measured values or values calculated from the raw materials used. The volume of particulate solid can be calculated from the mass and true density of the particulate solid used. The mass and true density of the particulate solid may be measured values or values calculated from the raw materials used. For example, the mass and true density of the particulate solid can be measured by separating the particulate solid from the non-particulate solid components from the non-volatile components of the composition and using the separated particulate solid.
[0025] The flash point of this composition is preferably 38°C or higher, more preferably 40°C or higher, and even more preferably 42°C or higher, with an upper limit of, for example, 150°C. This composition, with a flash point within the aforementioned range, offers excellent handling and storage advantages, making it suitable for use in ships and the like. In this specification, the flash point is measured in accordance with the description in JIS K 2265-2:2007.
[0026] This composition may contain volatile organic compounds (VOCs), but the VOC content in this composition is preferably 270 g / L or less, more preferably 250 g / L or less, and even more preferably 200 g / L or less, with a lower limit of, for example, 0 g / L, in order to create a composition that has little impact on the natural environment and the painting work environment.
[0027] In this specification, the VOC content in a composition can be calculated using the following formula (2), based on the composition's specific gravity, heat residue percentage (mass ratio of non-volatile components), and moisture content. The composition's specific gravity, heat residue percentage, and moisture content may be measured values as shown below, or values calculated from the raw materials used. VOC content (g / L) = Specific gravity of composition × 1000 × (100 - percentage of residual material after heating - moisture content) / 100 ... (2)
[0028] Composition specific gravity (g / cm 3 ): A value calculated by filling a 100 mL specific gravity cup with the composition (in the case of a multi-component composition, the composition immediately after mixing each of the raw materials for the composition) under a temperature of 23°C, and weighing the mass of the composition.
[0029] Heating residue percentage (mass%): This value is calculated by measuring the heat residue and the mass of the wire after weighing 1 ± 0.1 g of the composition (in the case of a multi-component composition, the composition immediately after mixing each of the raw materials) onto a flat-bottomed dish, spreading it evenly using a wire of known mass, drying it at 23°C for 24 hours, and then heating it at a heating temperature of 125°C for 1 hour (under normal pressure). In this specification, the heating residue is referred to as "non-volatile content."
[0030] In this specification, in each component (e.g., epoxy resin) that constitutes the first agent, second agent, main agent, and curing agent, components other than organic solvents and water in each agent, such as the main agent, curing agent, first agent, and second agent, are referred to as "solids."
[0031] Moisture content (mass%): The value of the mass percentage of water contained in 100% by mass of the composition, measured by the Karl Fischer method.
[0032] <First agent> The first agent comprises epoxy resin (AN).
[0033] The epoxy equivalent of the solid content of the total epoxy compound contained in the first agent is 450 or less, preferably 300 or less, more preferably 270 or less, preferably 150 or more, and more preferably 180 or more. When the epoxy equivalent of the solid content of all epoxy compounds contained in the first agent is within the aforementioned range, a non-skid layer (non-skid laminate) with high non-skid properties and excellent impact resistance can be easily formed. Furthermore, if the first agent contains x mass% of epoxy compound A with epoxy equivalent a and y mass% of epoxy compound B with epoxy equivalent b, the epoxy equivalent of the solid content of all epoxy compounds in the first agent is calculated as (x+y) / (x / a+y / b). The same applies when the first agent contains three or more epoxy compounds. Furthermore, the epoxy compound refers to compounds having epoxy groups, such as the epoxy resin (AN) and reactive diluents listed below.
[0034] [Epoxy resin (AN)] Examples of epoxy resins (AN) include polymers or oligomers containing two or more epoxy groups in their molecule, or polymers or oligomers produced by a ring-opening reaction of those epoxy groups. One type of epoxy resin (AN) may be used, or two or more types may be used.
[0035] Examples of epoxy resins (AN) include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD type epoxy resin, glycidyl ether type epoxy resin, glycidyl ester type epoxy resin, glycidylamine type epoxy resin, phenol novolac type epoxy resin, cresol type epoxy resin, and aliphatic epoxy resin.
[0036] Specific examples of epoxy resins (AN) include epichlorohydrin-bisphenol A epoxy resin (bisphenol A diglycidyl ether type); epichlorohydrin-bisphenol AD epoxy resin; epichlorohydrin-bisphenol F epoxy resin; epoxy novolac resin; and alicyclic epoxy resins such as 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate.
[0037] Epoxy resin (AN) is preferably a resin containing an aromatic ring, more preferably a bisphenol A type epoxy resin or a bisphenol F type epoxy resin, and even more preferably a bisphenol A type epoxy resin, because it tends to easily form a non-skid layer (non-skid laminate) with excellent impact resistance.
[0038] Examples of bisphenol A type epoxy resins include condensate polymers of bisphenol A type diglycidyl ethers such as bisphenol A diglycidyl ether, bisphenol A (poly)propylene oxide diglycidyl ether, bisphenol A (poly)ethylene oxide diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, hydrogenated bisphenol A (poly)propylene oxide diglycidyl ether, and hydrogenated bisphenol A (poly)ethylene oxide diglycidyl ether.
[0039] The epoxy equivalent of the epoxy resin (AN) is preferably 50 to 1,000, more preferably 100 to 850, and even more preferably 150 to 700, from the viewpoint that a non-skid layer with excellent non-skid properties can be easily formed.
[0040] In this specification, epoxy equivalent is measured in accordance with JIS K 7236:2001. In this specification, epoxy equivalent refers to the epoxy equivalent per unit of solid content of the epoxy resin. For example, when preparing a composition, if a solution is used in which an epoxy resin that is semi-solid or solid at room temperature (as described later) is diluted with a solvent, the epoxy equivalent refers to the epoxy equivalent of the solid content in the solution. When using two or more types of epoxy resins, the epoxy equivalent of the epoxy resins is the total epoxy equivalent of the two or more epoxy resins. For example, if epoxy resin A with epoxy equivalent a is contained in x mass%, and epoxy resin B with epoxy equivalent b is contained in y mass%, the total epoxy equivalent of the epoxy resins is calculated as (x+y) / (x / a+y / b).
[0041] When using commercially available raw materials (e.g., epoxy resin (AN) or amine compound (BN)) in each composition described herein, the equivalent values of each raw material (e.g., epoxy equivalent or active hydrogen equivalent) may be those listed in the catalog of the commercially available product. Note that the equivalent values may be listed as a numerical range in the catalog of the commercially available product. When using a commercially available product in which the equivalent value is listed as a numerical range, this specification uses the median value of that numerical range as the equivalent value of the commercially available product.
[0042] The viscosity of epoxy resin (AN) at 25°C, as measured with an E-type viscometer (TOKIMEC, FMD type, rotation speed: 60 rpm), is preferably 1,500 mPa·s or higher, more preferably 3,000 mPa·s or higher, preferably 120,000 mPa·s or lower, and more preferably 30,000 mPa·s or lower.
[0043] The epoxy resin (AN) may be liquid, semi-solid, or solid at room temperature (25°C, the same applies hereafter), but it is preferable to use a liquid epoxy resin because it can reduce the VOC content in this composition. The epoxy resin (AN) may be synthesized by conventionally known methods, or a commercially available product may be used.
[0044] Examples of commercially available epoxy resins that are liquid at room temperature include "E-028" (manufactured by Ohtake Meishin Chemical Co., Ltd., bisphenol A type epoxy resin, epoxy equivalent 190, viscosity 12,000~15,000 mPa·s / 25℃) and "jER807" (manufactured by Mitsubishi Chemical Corporation, bisphenol F type epoxy resin, epoxy equivalent 167.5, viscosity 3,000~4,500 mPa·s / 25℃).
[0045] A commercially available epoxy resin that is semi-solid at room temperature is, for example, "jER834" (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 250).
[0046] Examples of commercially available epoxy resins that are solid at room temperature include "E-001-75X" (manufactured by Ohtake Meishin Chemical Co., Ltd., bisphenol A type epoxy resin, epoxy equivalent 475), "jER1001" (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 475), "jER1004" (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 925), and "jER1007" (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 1975).
[0047] You may also use solutions such as "E-834-85M" (manufactured by Ohtake Meishin Chemical Co., Ltd., a methyl amyl ketone solution of bisphenol A type epoxy resin (834 type epoxy resin solution), epoxy equivalent 250) and "E-001-75M" (manufactured by Ohtake Meishin Chemical Co., Ltd., a methyl amyl ketone solution of bisphenol A type epoxy resin, epoxy equivalent 475), which are epoxy resins that are semi-solid or solid at room temperature and have been diluted with a solvent.
[0048] The solid content of epoxy resin (AN) in the first agent is preferably 5 to 20% by mass, more preferably 8 to 17% by mass, and even more preferably 10 to 15% by mass, relative to 100% by mass of the solid content of the first agent, in order to suppress the shedding of aggregate powder and to easily form a non-skid layer with excellent non-skid properties.
[0049] The solid content of epoxy resin (AN) relative to 100% by mass of the nonvolatile content of this composition is preferably 6 to 18% by mass, more preferably 8 to 16% by mass, and even more preferably 10 to 14% by mass, in order to suppress the shedding of aggregate powder and to easily form a non-skid layer with excellent non-skid properties.
[0050] <Second drug> The second agent comprises an amine compound (BN), and the amine compound (BN) comprises an alicyclic amine compound. The amine compound (BN) is a compound having an amino group in its molecule, and is preferably a compound other than a tertiary amine (a compound having only a tertiary amino group as the amino group), and is preferably a polyamine having two or more primary or secondary amino groups in its molecule. The amine compound (BN) may be used individually or in combination of two or more types.
[0051] Examples of amine compounds (BNs) include aliphatic amines, alicyclic amines, aromatic amines, and heterocyclic amines. These amine compounds are distinguished by the type of carbon to which the amino group is bonded. For example, an aliphatic amine is a compound that has at least one amino group bonded to an aliphatic carbon.
[0052] Examples of aliphatic amine compounds include alkyl monoamines, alkylene polyamines, polyalkylene polyamines, polyoxyalkylene polyamines, and alkylaminoalkylamines, and preferably polyamines having two or more amino groups in the molecule, such as alkylene polyamines, polyalkylene polyamines, polyoxyalkylene polyamines, and alkylaminoalkylamines.
[0053] Examples of alkylene polyamines include those with the formula: "H2NR A -NH2" (R A A is a divalent hydrocarbon group having 1 to 12 carbon atoms. Examples of compounds represented by ( ) include methylenediamine, ethylenediamine (EDA), 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, and trimethylhexamethylenediamine.
[0054] Examples of polyalkylene polyamines include those with the formula: "H2N-(C m H 2m NH) nExamples of compounds represented by (H) (where m is an integer from 1 to 10, and n is an integer from 2 to 10, preferably from 2 to 6) include, specifically, diethylenetriamine, dipropylenetriamine, triethylenetetramine, tripylenetetramine, tetraethylenepentamine, tetrapropylenepentamine, pentaethylenehexamine, nonaethylenedecamine, and bis(hexamethylene)triamine.
[0055] Examples of polyoxyalkylene polyamines include polyoxyethylenediamine, polyoxypropylenediamine, polyoxypropylenetriamine, polyoxypropylene-polyoxyethylenediamine, trimethylolpropanepoly(oxypropylene)triamine, and glycerylpoly(oxypropylene)triamine.
[0056] Examples of alkylaminoalkylamines include those with the formula: "R B 2N-(CH2) p -NH2" (R B These are independently hydrogen atoms or C1-C8 alkyl groups (where at least one R) B A is an alkyl group having 1 to 8 carbon atoms, and p is an integer from 1 to 6. Examples of compounds represented by ) include dimethylaminoethylamine, diethylaminoethylamine, dibutylaminoethylamine, dimethylaminopropylamine, diethylaminopropylamine, dipropylaminopropylamine, dibutylaminopropylamine, and dimethylaminobutylamine.
[0057] Other aliphatic amine compounds include, for example, tetra(aminomethyl)methane, tetrakis(2-aminoethylaminomethyl)methane, 1,3-bis(2'-aminoethylamino)propane, bis(aminomethyl)cyclohexane (especially 1,3-bis(aminomethyl)cyclohexane), isophoronediamine, mensendiamine (MDA), o-xylylenediamine, m-xylylenediamine (MXDA), p-xylylenediamine, bis(aminomethyl)naphthalene, bis(aminoethyl)naphthalene, 1,4-bis(3-aminopropyl)piperazine, 1-(2'-aminoethylpiperazine), 1-[2'-(2''-aminoethylamino)ethyl]piperazine, 2,2'-[ethylenebis(iminotrimethyleneimino)]bis(ethaneamine), tris(2-aminoethyl)amine, and bis(cyanoethyl)diethylenetriamine.
[0058] Examples of alicyclic amine compounds include cyclohexanediamine (especially 1,4-cyclohexanediamine), diaminodicyclohexylmethane (especially 4,4'-methylenebis(cyclohexylamine)), 4,4'-isopropylidenebis(cyclohexylamine), and norbornanediamine.
[0059] Examples of aromatic amine compounds include aromatic polyamine compounds having two or more primary amino groups bonded to a benzene ring, specifically phenylenediamine, naphthalenediamine, diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 4,4'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylsulfone, 2,2'-dimethyl-4,4'-diaminodiphenylmethane, 2,4'-diaminobiphenyl, 2,3'-dimethyl-4,4'-diaminobiphenyl, and 3,3'-dimethoxy-4,4'-diaminobiphenyl.
[0060] Examples of heterocyclic amine compounds include 1,4-diazacycloheptane, 1,11-diazacycloeicosane, and 1,15-diazacyclooctacosane.
[0061] Examples of amine compounds (BN) include modified versions of the aforementioned amine compounds, such as polyamidoamines, amine adducts with epoxy compounds, Mannich modified products (e.g., Mannich modified aliphatic polyamines, Mannich modified aromatic polyamines, phenalkamines, phenalkamides), Michael adducts, ketimines, aldimines, and urethane modified products.
[0062] The amine compound (BN) is preferably composed of at least one selected from alicyclic amines and modified alicyclic amines, and an amine compound containing an aromatic ring, as these tend to easily form a non-skid layer (non-skid laminate) with superior impact resistance. The amine compound containing the aromatic ring is preferably polyamidoamine, an amine adduct of polyamidoamine and an epoxy compound, or a Mannich modified product.
[0063] The active hydrogen equivalent of the amine compound (BN) is preferably 50 or more, more preferably 80 or more, preferably 1,000 or less, and more preferably 500 or less, as it tends to easily form a non-skid layer (non-skid laminate) with excellent impact resistance. In this specification, the active hydrogen equivalent refers to the amount of active hydrogen per unit of solid content of the amine compound. For example, when an amine compound containing a solvent is used when preparing the second agent, the active hydrogen equivalent refers to the amount of active hydrogen in the solid content of the amine compound containing the solvent.
[0064] The amount of solids of the amine compound (BN) relative to 100% by mass of the nonvolatile content of this composition is preferably such that it satisfies the reaction ratio described below, more preferably 3 to 12% by mass, and even more preferably 3 to 10% by mass, in order to suppress the shedding of aggregate powder and to easily form a non-skid layer with excellent non-skid properties and abrasion resistance.
[0065] The amount of solids of the alicyclic amine compound relative to 100% by mass of the nonvolatile content of this composition is preferably such that it satisfies the following reaction ratio, more preferably 0.2 to 10% by mass, even more preferably 0.5 to 8% by mass, and particularly preferably 0.8 to 6% by mass. The solid content of the alicyclic amine compound relative to 100% by mass of the solid content of the amine compound (BN) is preferably 10 to 100% by mass, more preferably 15 to 100% by mass, and even more preferably 20 to 100% by mass. When the content of alicyclic amine compounds is within the aforementioned range, it tends to be possible to easily form a non-skid layer (non-skid laminate) with superior impact resistance.
[0066] The reaction ratio calculated by the following formula (3) in this composition is preferably 0.3 to 1.2, more preferably 0.3 to 1.0, and even more preferably 0.3 to 0.8, as it tends to easily form a non-skid layer (non-skid laminate) with excellent impact resistance. Reaction ratio = {(Amount of solid content of amine compound (BN) / Active hydrogen equivalent of amine compound (BN)) + (Amount of solid content of component reactive with epoxy resin (AN) / Functional group equivalent of solid content of component reactive with epoxy resin (AN))} / {(Amount of solid content of epoxy resin (AN) / Epoxy equivalent of epoxy resin (AN)) + (Amount of solid content of component reactive with amine compound (BN) / Functional group equivalent of solid content of component reactive with amine compound (BN))} ... (3)
[0067] In formula (3), the "component that is reactive to the amine compound (BN)" can be a compound having an epoxy group or a (meth)acryloyl group, and specific examples include silane coupling agents, reactive diluents, and polymerizable (meth)acrylate monomers. In addition, the "component that is reactive to the epoxy resin (AN)" in formula (3) can be a compound having a primary or secondary amino group, and specific examples include silane coupling agents. Since silane coupling agents having an amino group or an epoxy group as a reactive group can be used, it is necessary to determine whether the silane coupling agent is reactive with amine compounds (BN) or epoxy resins (AN) depending on the type of reactive group, and then calculate the reaction ratio.
[0068] In this specification, "functional group equivalent" means the mass (g) per mole of functional group obtained by dividing the mass of 1 mole of these components by the number of moles of functional groups contained therein.
[0069] [Additives] The composition (the first and / or second agent) may contain additives other than epoxy resin (AN) and amine compound (BN), as long as they do not impair the effects of the present invention. Examples of such additives include aggregates, pigments other than aggregates, adhesion enhancers, thixotropes (anti-sagging agents, anti-settling agents), reactive diluents, defoamers, curing accelerators, organic solvents, plasticizers, dehydrating agents (stabilizers), dispersants, leveling agents, film-forming aids, wetting agents, antifreeze agents, flame retardants, antifungal agents, UV absorbers, antioxidants, surfactants, antifouling agents, and water. Each additive may be used individually or in combination of two or more types.
[0070] This composition may contain crystalline silica, but the amount of crystalline silica in this composition is preferably 0.1% by mass or less, more preferably 0.05% by mass or less, with a lower limit of 0% by mass, based on 100% by mass of the nonvolatile content of this composition.
[0071] ·aggregate This composition preferably contains aggregate because it has a static friction coefficient within the aforementioned range and can easily form a non-skid layer with excellent non-skid properties. When incorporating aggregate, the aggregate may be incorporated into the first agent, into the second agent, or into both the first and second agents, but it is preferable to incorporate it into the first agent. The aggregate may be of one type or two or more types.
[0072] Examples of aggregates include aluminum oxide (alumina), silicon carbide, aluminum powder, slag obtained from blast furnaces, natural aggregates (e.g., andesite, silica, emery, basalt, quartz, molybdenum), and crushed ceramic particles. As for the aggregate, it is preferable to include at least one selected from aluminum oxide and aluminum powder, given that it tends to easily form a non-skid laminate with superior non-skid properties.
[0073] As for the aggregate, an aggregate with a Mohs hardness of 7 or higher is preferred because it tends to easily form a non-skid laminate with superior abrasion resistance. The Mohs hardness can be measured according to a 10-point Mohs hardness tester.
[0074] The shape of the aggregate is not particularly limited, and various shapes such as spherical, needle-shaped, plate-shaped, and flaky aggregates can be used, but aggregates with sharp edges are preferred. The average particle size of the aggregate is preferably 0.1 to 3.0 mm, more preferably 0.2 to 2.5 mm, and even more preferably 0.3 to 2.0 mm. In this specification, the average particle size of the aggregate is defined as the nominal sieve opening value when the cumulative mass fraction reaches 50%, as measured in accordance with JIS R 6001:2017.
[0075] If the composition contains aggregate, the aggregate content is preferably 15 to 70% by mass, more preferably 20 to 60% by mass, and even more preferably 25 to 55% by mass, based on 100% by mass of the nonvolatile content of the composition. Furthermore, if the first agent contains aggregate, the aggregate content is preferably 15% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, preferably 70% by mass or less, and more preferably 65% by mass or less, based on 100% by mass of the solid content of the first agent. When the aggregate content is within the aforementioned range, the shedding of aggregate powder can be suppressed, and a non-skid layer with excellent non-skid properties can be easily formed. In particular, when the aggregate content is above the aforementioned lower limit, the aggregate is sufficiently exposed on the surface of the non-skid laminate (non-skid layer), making it easy to form a non-skid laminate (non-skid layer) with the desired static friction coefficient and non-skid properties (anti-slip properties). When the aggregate content is below the aforementioned upper limit, it is difficult to form a porous non-skid layer, and therefore a non-skid layer with excellent corrosion resistance can be easily formed. Furthermore, because the cohesive force of the non-skid layer does not easily decrease, a non-skid layer that is less prone to cracks and other fissures can be easily formed.
[0076] Pigments This composition preferably contains pigments other than aggregates. These pigments may be incorporated into the first component, the second component, or the third component. Examples of pigments used in this composition include extender pigments and coloring pigments. The pigments may be either organic or inorganic. If this composition contains a pigment, the amount of the pigment is PVC N It is preferable that the amount is such that it falls within the aforementioned range. One type of pigment may be used, or two or more types may be used.
[0077] Examples of extender pigments include feldspars (e.g., potassium feldspar, orthoclase, microcline, soda feldspar, anorthite), zinc oxide, flattened pigments (e.g., talc, mica, aluminum flakes), barium sulfate (e.g., precipitated barium sulfate), anhydrous gypsum, hemihydrate gypsum, kaolin, bentonite, wollastonite, clay, aluminum hydroxide, magnesium carbonate, barium carbonate, heavy calcium carbonate, precipitated calcium carbonate, and dolomite. The shape of the extender pigment is not particularly limited, and pigments of various shapes such as spherical, needle-shaped, plate-shaped, flake-shaped, and fibrous can be used.
[0078] When this composition contains an extender pigment, the amount of the extender pigment is preferably 15 to 45% by mass, more preferably 20 to 35% by mass, relative to 100% by mass of the nonvolatile content of this composition, in order to easily form a non-skid layer with excellent film-forming properties and corrosion resistance.
[0079] Examples of coloring pigments include inorganic pigments such as carbon black, titanium dioxide (titanium white), iron oxide (red iron oxide), yellow iron oxide, flaky iron oxide, and ultramarine, as well as organic pigments such as cyanine blue and cyanine green. It is preferable to use titanium dioxide and / or carbon black as the coloring pigment.
[0080] If the composition contains a coloring pigment, the amount of the coloring pigment is preferably 1 to 30% by mass, more preferably 1 to 15% by mass, based on 100% by mass of the non-volatile content of the composition.
[0081] • Shaxuhm This composition preferably contains a thixotropizing agent (anti-sagging agent, anti-settling agent). When a quinotropant is incorporated, the quinotropant may be incorporated into the first agent, the second agent, or both the first and second agents, but it is preferable to incorporate it into both the first and second agents. One type of thixotrope may be used, or two or more types may be used.
[0082] Examples of conventionally known thixotropes include organic clay waxes such as stearate salts, lecithin salts, and alkyl sulfonates of Al, Ca, and Zn; organic waxes such as polyethylene wax, oxidized polyethylene wax, amide wax, polyamide wax, and hydrogenated castor oil wax; and synthetic fine silica.
[0083] As the thixotrope used in this composition, amide wax, synthetic fine silica, and polyethylene oxide wax are preferred, as they tend to easily produce compositions with excellent storage stability and easily form non-skid laminates with excellent non-skid properties. It is more preferable to use two or more of these, and even more preferable to include powdered amide wax and at least one selected from amide paste, polyethylene oxide wax, and synthetic fine silica.
[0084] Examples of thixotropes include "Disparon RE-9000," "Disparon 305," "Disparon A630-20X," "Disparon 6900-20X," "Disparon 4200-20," and "Disparon 6650" from Kusumoto Chemical Co., Ltd., "ASA D-120," "ASA T-250F," and "ASA T-55-20BX" from Ito Oil Co., Ltd., "Bentone 27" from Elementis Specialties, Inc., "CLAYTONE-MPZ" from BYK USA Inc., "BYK-410" from BYK-Chemie GmbH, and "AEROSIL R972" from Nippon Aerosil Co., Ltd.
[0085] If the composition contains a shaken agent, the solid content of the shaken agent is preferably 0.1 to 5% by mass relative to 100% by mass of the solid content of the composition.
[0086] • Reactive diluent The composition (particularly the first agent) may contain a reactive diluent, and is preferable, for the purpose of easily obtaining a low-viscosity, non-skid composition. As the reactive diluent, an epoxy group-containing reactive diluent is preferred. When using an epoxy group-containing reactive diluent as the reactive diluent, it is preferable to incorporate the reactive diluent into the first agent. The reactive diluent may be one type or two or more types.
[0087] The epoxy equivalent of the epoxy group-containing reactive diluent is preferably 50 to 1,000, more preferably 100 to 850, and even more preferably 120 to 700, from the viewpoint that a low viscosity composition can be easily obtained.
[0088] The reactive diluent is a compound other than the epoxy resin (AN) and the amine compound (BN), and may be monofunctional or polyfunctional. The viscosity of the reactive diluent at 25°C, as measured with an E-type viscometer (TOKIMEC, FMD type, rotation speed: 60 rpm), is preferably 500 mPa·s or less.
[0089] Examples of monofunctional epoxy group-containing reactive diluents include alkyl glycidyl ethers (preferred examples of alkyl groups: 1 to 13 carbon atoms), phenyl glycidyl ethers, o-cresyl glycidyl ethers, alkylphenyl glycidyl ethers (preferred examples of alkyl groups: 1 to 20 carbon atoms, preferably 1 to 5 carbon atoms, e.g., methylphenyl glycidyl ether, ethylphenyl glycidyl ether, propylphenyl glycidyl ether, p-tert-butylphenyl glycidyl ether), phenol glycidyl ethers, alkylphenol glycidyl ethers, and phenol (EO). n Examples include glycidyl ethers (number of repeats n=3-20, EO:-C2H4O-), alkyl glycidyl esters (preferred examples of alkyl groups: 3-10 carbon atoms), and polyglycol glycidyl ethers.
[0090] Examples of polyfunctional epoxy group-containing reactive diluents include 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, resorcinol diglycidyl ether, polyglycol diglycidyl ether, mono- or polyalkylene glycol diglycidyl ether (preferred examples of alkylene groups: 1 to 5 carbon atoms, e.g., ethylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether), trimethylolpropane triglycidyl ether, alkyl diglycidyl ether, and alkyl diglycidyl ester. Preferred examples of the alkyl group include alkyl groups having 3 to 10 carbon atoms, specifically, alkyl groups such as neopentyl group and 2-ethylhexyl group.
[0091] If the composition contains a reactive diluent, the solid content of the reactive diluent is preferably 0.1 to 10% by mass, more preferably 0.5 to 8% by mass, and even more preferably 1.0 to 5% by mass, based on 100% by mass of the nonvolatile content of the composition. When the content of the reactive diluent is within the aforementioned range, a non-skid layer with excellent oil resistance, solvent resistance, and chemical resistance can be easily formed, contributing to a reduction in the viscosity of the composition.
[0092] • Curing accelerator This composition (particularly the second component) may optionally contain a curing accelerator for purposes such as promoting drying and curing when forming a non-skid layer. Examples of curing accelerators include polymerizable (meth)acrylate monomers and tertiary amines. When using polymerizable (meth)acrylate monomers, they should be added to the first component; when using tertiary amines, they should be added to the second component. The hardening accelerator may be one type or two or more types.
[0093] Examples of commercially available polymerizable (meth)acrylate monomers include "M-CURE 100" (monofunctional aromatic acrylate, functional group equivalent 257-267), "M-CURE 200" (difunctional aromatic acrylate, functional group equivalent 130-140), "M-CURE 201" (difunctional aliphatic acrylate, functional group equivalent 95-105), "M-CURE 300" (trifunctional aliphatic acrylate, functional group equivalent 112-122), "M-CURE 400" (tetrafunctional aliphatic acrylate, functional group equivalent 80-90), and "M-CURE 400NS" (tetrafunctional aliphatic acrylate, functional group equivalent 80-90) (all manufactured by SARTOMER (Guangzhou) Chemicals Ltd.).
[0094] Specific examples of the aforementioned tertiary amines include triethanolamine, dialkylaminoethanol, triethylenediamine (1,4-diazabicyclo[2.2.2]octane), and 2,4,6-tris(dimethylaminomethyl)phenol. A commercially available example is "Ancamine K-54" (manufactured by Evonik, 2,4,6-tri(dimethylaminomethyl)phenol).
[0095] If the composition contains a curing accelerator, the solid content of the curing accelerator is preferably 0.1 to 5% by mass relative to 100% by mass of the nonvolatile content of the composition.
[0096] • Organic solvents Examples of the aforementioned organic solvents include aromatic hydrocarbon solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and methyl amyl ketone (MAK); ether solvents such as butyl cellosolve; ester solvents such as butyl acetate; alcohol solvents such as isopropanol, isobutyl alcohol, n-butanol, and propylene glycol monomethyl ether (PGM); and aliphatic hydrocarbon solvents such as n-hexane, n-octane, 2,2,2-trimethylpentane, isooctane, n-nonane, cyclohexane, and methylcyclohexane. One type of organic solvent may be used, or two or more types may be used.
[0097] If this composition contains an organic solvent, it is preferable to use an organic solvent such that the VOC content in this composition falls within the aforementioned range. The composition is preferably an organic solvent-based composition, and the content of the organic solvent in the composition is preferably 0.1 to 20% by mass, more preferably 2 to 15% by mass, and even more preferably 4 to 10% by mass, based on 100% by mass of the composition.
[0098] The first agent is preferably an organic solvent-based agent, and the content of the organic solvent in the first agent is preferably 2 to 10% by mass relative to 100% by mass of the first agent. The second agent is preferably an organic solvent-based agent, and the content of the organic solvent in the second agent is preferably 0.5 to 10% by mass relative to 100% by mass of the second agent.
[0099] [Method for preparing this composition] This composition, the first agent, the second agent, etc., can be prepared by mixing (kneading) the raw materials to be incorporated into them. When mixing (kneading), the raw materials may be added and mixed all at once, or they may be added and mixed in multiple stages. This composition can be prepared by mixing (kneading) the aforementioned first agent and second agent, etc. During the mixing (kneading) process, conventionally known devices such as mixers, dispersers, and agitators can be used. Examples of such devices include dispersers, mortar mixers, and planetary mixers. Furthermore, the mixing (kneading) process may be carried out while heating, cooling, etc., depending on the season, environment, etc.
[0100] ≪Non-skid layer≫ The non-skid layer is a layer formed from this composition, having a surface static friction coefficient of 0.80 or higher.
[0101] The static friction coefficient of the surface of the non-skid layer is 0.80 or higher, preferably 0.85 or higher, more preferably 0.90 or higher, with an upper limit of, for example, 1.30. When the static friction coefficient falls within the aforementioned range, it can be said to have high non-skid properties, and even when the non-skid layer is used on a vehicle deck or flight deck, it can sufficiently suppress the sliding of vehicles, aircraft, etc. For this reason, this laminate with a static friction coefficient within the aforementioned range can be suitably used on ships, especially on vehicle decks and flight decks, and is particularly suitable for use on the decks of warships. The non-skid layer is usually provided on a base material such as a vehicle deck or flight deck, and in this case, it is preferable that the coefficient of static friction on the surface opposite to the base material is within the aforementioned range. The static friction coefficient is specifically measured by the method described in the following embodiment.
[0102] The non-skid layer is preferably applied in an amount of 1,000 to 5,000 g / m². 2 More preferably 1,800 to 4,500 g / m² 2 More preferably 2,200 to 4,300 g / m² 2 It is desirable that the layer be formed in such a manner. When the thickness and amount of the non-skid layer are within the aforementioned range, it tends to be possible to easily form a non-skid laminate with excellent non-skid properties and impact resistance.
[0103] The non-skid layer is specifically formed by drying (curing) this composition. There are no particular restrictions on the conditions for forming the non-skid layer; these can be set appropriately depending on the method of forming the non-skid layer, its application, the painting environment, etc. The drying (curing) temperature is typically 5 to 40°C when drying (curing) at room temperature, and typically 30°C or higher and less than 100°C, more preferably 40 to 80°C, when forced drying (curing) is performed using a hot air dryer or the like. The drying (curing) time varies depending on the drying (curing) method. For room temperature drying, it takes approximately 1 to 30 days, while for forced drying, it takes approximately 3 hours to 7 days.
[0104] ≪Non-skid laminate≫ The non-skid laminate according to the present invention (hereinafter also referred to as "this laminate") comprises a primer layer and the non-skid layer. In this laminate, it is preferable that the static friction coefficient of the non-skid layer on the surface opposite to the primer layer is within the aforementioned range.
[0105] The non-skid layer is typically a layer provided on the side opposite to the substrate of the primer layer, and is typically a layer that constitutes the surface of the laminate formed on the substrate. This laminate may contain two or more non-skid layers, but usually it contains one.
[0106] The laminate may have layers other than the primer layer and the non-skid layer, but from the viewpoint of adhesion to the substrate and corrosion resistance, it is preferable that the primer layer is in contact with the substrate, and from the viewpoint of non-skid properties, it is preferable that the non-skid layer is on the surface of the substrate (the surface opposite to the substrate side of the primer layer). In one embodiment of the present invention, it is preferable that the primer layer and the non-skid layer are in contact.
[0107] The aforementioned PVC N and the volume concentration of particulate solids in the primer layer (PVC P ) is the difference with PVC N -PVC P Preferably, it is 19.0% or more, more preferably 22% or more, even more preferably 25% or more, particularly preferably 29% or more, preferably 47% or less, and more preferably 40% or less. PVC N -PVC P When the range is as described above, it tends to be possible to easily form a non-skid laminate with excellent impact resistance. PVC N -PVC PAccording to this laminate, which falls within the aforementioned range, the cohesive force of the primer layer does not become excessively small compared to the cohesive force of the non-skid layer. Therefore, even if this laminate is subjected to impact, the problematic rupture (cohesive failure) of the primer layer itself is unlikely to occur, and only cohesive failure of the non-skid layer, which does not pose a major problem, may occur, thus achieving the desired effect.
[0108] <Primer layer> The primer layer is typically a layer provided on the substrate side of the non-skid layer. Depending on the type of substrate, when this laminate is used on ships, especially on vehicle decks or flight decks, the primer layer is preferably a so-called corrosion-resistant layer (corrosion-resistant coating). This laminate may contain two or more primer layers, but usually it contains one.
[0109] PVC P Preferably, it is 32.0% or less, more preferably 31% or less, even more preferably 30% or less, particularly preferably 29% or less, preferably 20% or more, more preferably 22% or more. PVC P When the coefficient is within the aforementioned range, blistering and cracking are suppressed, and a non-skid laminate with excellent adhesion to the substrate due to stress relaxation and excellent impact resistance can be easily formed.
[0110] The thickness of the primer layer (dry film thickness) is preferably 50 to 400 μm, more preferably 100 to 300 μm, and even more preferably 150 to 250 μm. When the thickness of the primer layer is within the aforementioned range, it tends to be possible to easily form a non-skid laminate with excellent corrosion resistance and impact resistance.
[0111] The primer layer is preferably a layer formed from a primer composition, and more preferably a layer formed from an epoxy resin-based primer composition, in order to better exhibit the effects of the present invention. The primer composition may be a one-component composition or a multi-component composition containing a main component and a curing agent, but it is preferably a multi-component composition, and more preferably a composition containing a main component containing an epoxy resin (AP) and a curing agent containing an amine compound (BP).
[0112] The aforementioned multi-component composition is not particularly limited as long as it is a multi-component composition containing a main component and a curing agent. It may also be a two-component composition consisting of a main component and a curing agent, and depending on the components used, it may be a three-component or more composition containing a third component other than the main component and curing agent. However, from the viewpoint of ease of formation of the laminate, a two-component composition is preferred. The aforementioned main component, hardener, and third component (hereinafter collectively referred to as "component n") are usually stored, preserved, and transported in separate containers, and are mixed together to form the composition when using a multi-component composition (e.g., immediately before painting) before use.
[0113] The flash point of the primer composition is preferably 35°C or higher, more preferably 38°C or higher, and even more preferably 40°C or higher, with an upper limit of, for example, 150°C. Primer compositions with flash points within the aforementioned range offer excellent handling and storage advantages, making them suitable for use in ships and the like.
[0114] The primer composition may contain volatile organic compounds (VOCs), but the VOC content in the primer composition is preferably 340 g / L or less, more preferably 320 g / L or less, and even more preferably 310 g / L or less, with a lower limit of, for example, 0 g / L, in order to create a composition that has little impact on the natural environment and the painting work environment.
[0115] The primer composition may contain crystalline silica, but the content of crystalline silica in the primer composition is preferably 0.1% by mass or less, more preferably 0.05% by mass or less, with a lower limit of 0% by mass, based on 100% by mass of the nonvolatile content of the primer composition.
[0116] [Epoxy resin (AP)] The main component preferably contains epoxy resin (AP). Examples of epoxy resins (AP) include compounds similar to those exemplified as epoxy resins (AN) above, and preferred compounds are also similar. One type of epoxy resin (AP) may be used, or two or more types may be used.
[0117] Furthermore, as the epoxy resin (AP), it is preferable to use epoxy resins other than modified epoxy resins (pure epoxy), such as alkyd-modified epoxy resins, fatty acid-modified epoxy resins, urethane-modified epoxy resins, amine-modified epoxy resins, acrylic-modified epoxy resins, polyester-modified epoxy resins, fatty acid-modified epoxy resins, phenol-modified epoxy resins, phosphate compound-modified epoxy resins, epoxidized oil-based epoxy resins, and brominated epoxy resins, because they tend to easily form non-skid laminates with excellent impact resistance. The amount of the modified epoxy resin in the main component relative to 100% by mass of the main component (the amount of the modified epoxy resin in the primer layer relative to 100% by mass of the primer layer) is preferably 0 to 10% by mass, more preferably 0 to 7% by mass, and even more preferably 0 to 5% by mass, from the standpoint that it tends to easily form a non-skid laminate with excellent impact resistance.
[0118] Epoxy resins (AP) tend to easily form non-skid laminates with excellent impact resistance and can easily form primer layers with superior corrosion resistance. For these reasons, resins containing aromatic rings are preferred, more preferably bisphenol A type epoxy resins or bisphenol F type epoxy resins, and even more preferably bisphenol A type epoxy resins.
[0119] Bisphenol A type epoxy resins are graded according to their structure, physical properties, and other characteristics. As one embodiment of the epoxy resin (AP), among the graded bisphenol A type epoxy resins, it is preferable to use an epoxy resin of grade 1001 or higher, as it tends to easily form a non-skid laminate with excellent impact resistance; it is preferable to use an epoxy resin of grade 834 or lower, as it has excellent paintability and allows for easy acquisition of a low-VOC primer composition; and it is preferable to use an epoxy resin of grade 1001 or higher and an epoxy resin of grade 834 or lower in combination, as it can achieve both of these effects. Examples of epoxy resins of grade 1001 or higher include epoxy resins of grades 1001, 1002, 1003, 1004, 1007, 1009, and 1010, while examples of epoxy resins of grade 834 or lower include epoxy resins of grades 834, 828, and 827.
[0120] When using epoxy resin of grade 1001 or higher and epoxy resin of grade 834 or lower, the ratio of the amount of solids of epoxy resin of grade 834 or lower to the amount of solids of epoxy resin of grade 1001 or higher (epoxy resin of grade 834 or lower / epoxy resin of grade 1001 or higher) is preferably 0.1 or more and less than 5.0, more preferably 0.3 to 2.0, on a mass basis. When the ratio of epoxy resin of grade 1001 or higher to epoxy resin of grade 834 or lower is within the aforementioned range, it tends to be possible to easily form a non-skid laminate with excellent adhesion to the substrate after impact.
[0121] The epoxy equivalent of the epoxy resin (AP) is preferably 50 to 1,000, more preferably 100 to 850, and even more preferably 150 to 700, from the viewpoint that a primer layer with excellent corrosion resistance can be easily formed.
[0122] The viscosity of epoxy resin (AP) measured at 25°C using an E-type viscometer (TOKIMEC, FMD type, rotation speed: 60 rpm) is preferably 1,500 mPa·s or higher, more preferably 3,000 mPa·s or higher, preferably 120,000 mPa·s or lower, and more preferably 30,000 mPa·s or lower.
[0123] The epoxy resin (AP) may be liquid, semi-solid, or solid at room temperature (25°C, the same applies hereafter). The epoxy resin (AP) may be synthesized by conventionally known methods, or a commercially available product may be used. Examples of such commercially available products include those similar to those exemplified in the section on epoxy resin (AN).
[0124] The solid content of epoxy resin (AP) in the main component is preferably 27 to 60% by mass, more preferably 29 to 56% by mass, and even more preferably 33 to 52% by mass, based on 100% by mass of the solid content of the main component, in order to easily form a primer layer with excellent corrosion resistance.
[0125] The content of epoxy resin (AP) solids relative to 100% by mass of nonvolatile content in the primer composition is preferably 24 to 50% by mass, more preferably 26 to 46% by mass, and even more preferably 29 to 42% by mass, from the viewpoint that a primer layer with excellent corrosion resistance can be easily formed.
[0126] [Amine compounds (BP)] The curing agent preferably contains an amine compound (BP). The amine compound (BP) is a compound having an amino group in its molecule, and is preferably a compound other than a tertiary amine (a compound having only a tertiary amino group as the amino group), and is preferably a polyamine having two or more primary or secondary amino groups in its molecule. Examples of amine compounds (BP) include compounds similar to those exemplified as amine compounds (BN) above. The amine compound (BP) may be used individually or in combination of two or more types.
[0127] As for amine compounds (BP), compounds containing rings are preferred because they tend to easily form non-skid laminates with excellent impact resistance and can easily form primer layers with superior corrosion resistance, and polyamidoamines, amine adducts of polyamidoamines and epoxy compounds, and Mannich-modified products are more preferred, phenalkamine is even more preferred, and phenalkamine obtained using ethylenediamine is particularly preferred.
[0128] The active hydrogen equivalent of the amine compound (BP) is preferably 50 or more, more preferably 80 or more, preferably 1,000 or less, and more preferably 500 or less, from the viewpoint that it is possible to easily form a primer layer with excellent corrosion resistance.
[0129] The amount of solids of the amine compound (BP) relative to 100% by mass of the nonvolatile content of the primer composition is preferably such that it satisfies the following reaction ratio, more preferably 6 to 20% by mass, and even more preferably 8 to 15% by mass, in order to easily form a primer layer with excellent corrosion resistance.
[0130] The reaction ratio calculated by the following formula (4) in the primer composition is preferably 0.3 to 1.2, more preferably 0.3 to 1.0, and even more preferably 0.3 to 0.8, as it tends to easily form a primer layer with excellent corrosion resistance and a non-skid laminate with excellent impact resistance. Reaction ratio = {(Amount of solid content of amine compound (BP) / Active hydrogen equivalent of amine compound (BP)) + (Amount of solid content of component reactive with epoxy resin (AP) / Functional group equivalent of solid content of component reactive with epoxy resin (AP))} / {(Amount of solid content of epoxy resin (AP) / Epoxy equivalent of epoxy resin (AP)) + (Amount of solid content of component reactive with amine compound (BP) / Functional group equivalent of solid content of component reactive with amine compound (BP))} ... (4)
[0131] In formula (4), the "component that is reactive to the amine compound (BP)" can be a compound having an epoxy group or a (meth)acryloyl group, and specific examples include silane coupling agents, reactive diluents, and polymerizable (meth)acrylate monomers. In addition, the "component that is reactive to the epoxy resin (AP)" in formula (4) can be a compound having a primary or secondary amino group, and specific examples include silane coupling agents. Since silane coupling agents having an amino group or an epoxy group as a reactive group can be used, it is necessary to determine whether the silane coupling agent is reactive with amine compounds (BP) or epoxy resins (AP) depending on the type of reactive group, and then calculate the reaction ratio.
[0132] [Additives] The primer composition (main component and / or curing agent) may contain additives other than epoxy resin (AP) and amine compound (BP) to the extent that it does not impair the effects of the present invention. Examples of such additives include pigments, adhesion enhancers, thixotropes (anti-sagging agents, anti-settling agents), reactive diluents, defoamers, curing accelerators, organic solvents, plasticizers, dehydrating agents (stabilizers), dispersants, leveling agents, film-forming aids, wetting agents, antifreeze agents, flame retardants, antifungal agents, UV absorbers, antioxidants, surfactants, antifouling agents, and water. Specific examples of pigments, thixotropes (anti-sagging agents, anti-settling agents), reactive diluents, curing accelerators, and organic solvents include the same components as those listed in the section on this composition. Each additive may be used individually or in combination of two or more types.
[0133] The primer composition (main component and / or curing agent) may contain a non-reactive resin, but the content of the solids of the non-reactive resin in the primer composition relative to 100% by mass of the non-volatile content of the primer composition (the content of the non-reactive resin in the primer layer relative to 100% by mass of the primer layer) is preferably 0 to 10% by mass, more preferably 0 to 7% by mass, and even more preferably 0 to 5% by mass, from the standpoint that a non-skid laminate with excellent impact resistance can be easily formed. The term "non-reactive resin" refers to non-reactive resins other than epoxy resins (AP) and amine compounds (BP) (resins that do not participate in the reaction between epoxy groups and amino groups, that is, resins that do not have epoxy groups, (meth)acryloyl groups, and primary or secondary amino groups).
[0134] Pigments The primer composition preferably contains a pigment. In the case of a multi-component primer composition, the pigment may be incorporated into the main component, the curing agent, or the third component. Examples of pigments used in the primer composition include extender pigments, coloring pigments, and rust-preventive pigments. The pigments may be either organic or inorganic. If the primer composition contains a pigment, the amount of the pigment is PVC P It is preferable that the amount is such that it falls within the aforementioned range. One type of pigment may be used, or two or more types may be used.
[0135] The aforementioned primer composition preferably contains a flattened pigment, as it allows for the easy formation of a primer layer with excellent corrosion resistance. Furthermore, the primer composition is preferably made up of feldspars, and more preferably soda feldspar, because it tends to easily form a non-skid laminate with excellent impact resistance.
[0136] If the primer composition contains an extender pigment, the amount of the extender pigment is preferably 30 to 60% by mass, more preferably 33 to 55% by mass, relative to 100% by mass of the nonvolatile content of the primer composition, in order to easily form a primer layer with excellent corrosion resistance.
[0137] If the primer composition contains a coloring pigment, the amount of the coloring pigment is preferably 1 to 20% by mass, more preferably 1 to 15% by mass, based on 100% by mass of the non-volatile content of the primer composition.
[0138] Examples of rust-preventive pigments include zinc powder, zinc alloy powder, zinc phosphate compounds, calcium phosphate compounds, aluminum phosphate compounds, magnesium phosphate compounds, zinc phosphite compounds, calcium phosphite compounds, aluminum phosphite compounds, strontium phosphite compounds, aluminum tripolyphosphate compounds, molybdate compounds, zinc cyanamide compounds, borate compounds, nitro compounds, and complex oxides.
[0139] If the primer composition contains a rust-preventive pigment, the amount of the rust-preventive pigment is preferably 0.5 to 20% by mass, more preferably 1 to 10% by mass, based on 100% by mass of the non-volatile content of the primer composition.
[0140] • Adhesion enhancer The aforementioned primer composition is preferably equipped with an adhesion enhancer, as it tends to easily form a primer layer with excellent adhesion to the substrate and excellent corrosion resistance, as well as a non-skid laminate with excellent impact resistance. Examples of adhesion-enhancing agents include organic acids, chelating agents, and silane coupling agents, with silane coupling agents being preferred among these. The adhesion enhancer may be of one type or of two or more types.
[0141] The silane coupling agent is not particularly limited, and conventionally known compounds can be used. Preferably, the silane coupling agent is a compound that has at least two functional groups within the same molecule and can contribute to improving adhesion to the substrate, reducing the viscosity of the primer composition, etc. For example, such a compound is: "X-SiMe" n Y 3-n Examples of compounds represented by (n is 0 or 1, X is a reactive group capable of reacting with organic matter, Me is a methyl group, and Y is a hydrolyzable group) include: Examples of X include amino groups, vinyl groups, epoxy groups, mercapto groups, halogen groups, groups in which part of a hydrocarbon group is substituted with these groups, and groups in which part of a hydrocarbon group is substituted with an ether bond or the like, and part of these groups is substituted with these groups. When using a silane coupling agent in a primer composition, it is appropriate to select whether to use it in the main component or the curing agent depending on the type of X. Examples of Y include alkoxy groups such as methoxy groups and ethoxy groups.
[0142] The silane coupling agent is preferably a compound having an epoxy group or an amino group as a reactive group, and more preferably a compound having an epoxy group. Examples of commercially available silane coupling agents include "KBM-403" (γ-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.) and "Sylace S-510" (manufactured by JNC Corporation).
[0143] If the primer composition contains an adhesion enhancer, the solid content of the adhesion enhancer is preferably 0.05 to 10% by mass, more preferably 0.1 to 8% by mass, and even more preferably 0.15 to 5% by mass, based on 100% by mass of the nonvolatile content of the primer composition. When the content of the adhesion enhancer is within the aforementioned range, the performance of the primer layer, such as adhesion to the substrate, is improved, and the viscosity of the primer composition can be reduced. As a result, painting workability is improved, and a non-skid laminate with excellent impact resistance tends to be easily formed.
[0144] • Shaxuhm The primer composition (particularly the main component) preferably contains a thixotropizing agent (anti-sagging agent, anti-settlement agent). One type of thixotrope may be used, or two or more types may be used.
[0145] If the primer composition contains a thixotrope, the solid content of the thixotrope is preferably 0.1 to 5% by mass relative to 100% by mass of the solid content of the primer composition.
[0146] • Reactive diluent The primer composition (especially the main component) may contain a reactive diluent for purposes such as easily obtaining a low-viscosity primer composition. As a reactive diluent, an epoxy group-containing reactive diluent is preferred. When using an epoxy group-containing reactive diluent, it is preferable to incorporate the reactive diluent into the main component. The reactive diluent may be one type or two or more types.
[0147] The epoxy equivalent of the epoxy group-containing reactive diluent is preferably 50 to 1,000, more preferably 100 to 850, and even more preferably 120 to 700, from the viewpoint that a low viscosity primer composition can be easily obtained.
[0148] The reactive diluent is a compound other than the epoxy resin (AP) and the amine compound (BP), and may be monofunctional or polyfunctional. The viscosity of the reactive diluent at 25°C, as measured with an E-type viscometer (TOKIMEC, FMD type, rotation speed: 60 rpm), is preferably 500 mPa·s or less.
[0149] If the primer composition contains a reactive diluent, the solid content of the reactive diluent is preferably 0.1 to 10% by mass, more preferably 0.5 to 8% by mass, and even more preferably 1 to 5% by mass, based on 100% by mass of the nonvolatile content of the primer composition. When the content of the reactive diluent is within the aforementioned range, a primer layer with excellent oil resistance, solvent resistance, chemical resistance, and corrosion resistance can be easily formed, and this contributes to reducing the viscosity of the primer composition.
[0150] • Antifoaming agent The primer composition preferably contains an antifoaming agent, as this can suppress the generation of bubbles during the manufacturing or application of the composition, or break bubbles that have been generated in the primer composition, and allow for the easy formation of a primer layer with desired physical properties. One type of defoaming agent may be used, or two or more types may be used.
[0151] Commercially available products may be used as the antifoaming agent, and examples of such products include "BYK-392", "BYK-066N", "BYK-1770", "BYK-1790" (all manufactured by Bic Chemie Japan Co., Ltd.), "TEGO Airex 902W" (manufactured by Evonik), and "Spectrasyn 40" (manufactured by Exxonmobil Chemical Company).
[0152] If the primer composition contains an antifoaming agent, the solid content of the antifoaming agent is preferably 0.005 to 3% by mass, more preferably 0.01 to 2% by mass, based on 100% by mass of the nonvolatile content of the primer composition. When the antifoaming agent content is within the aforementioned range, foam generation can be sufficiently suppressed, and a primer layer with the desired physical properties can be easily formed.
[0153] • Curing accelerator The primer composition (particularly the curing agent) may optionally contain a curing accelerator for purposes such as promoting drying and curing when forming the primer layer. Examples of curing accelerators include polymerizable (meth)acrylate monomers and tertiary amines. When using polymerizable (meth)acrylate monomers, they are incorporated into the main component; when using tertiary amines, they are incorporated into the curing agent. The hardening accelerator may be one type or two or more types.
[0154] If the primer composition contains a curing accelerator, the solid content of the curing accelerator is preferably 0.1 to 5% by mass relative to 100% by mass of the nonvolatile content of the primer composition.
[0155] • Organic solvents If the primer composition contains one or more organic solvents, it is preferable to use organic solvents such that the VOC content in the primer composition falls within the specified range. The primer composition is preferably an organic solvent-based composition, and the content of the organic solvent in the primer composition is preferably 3 to 30% by mass, more preferably 5 to 27% by mass, and even more preferably 10 to 24% by mass, based on 100% by mass of the primer composition.
[0156] The main component is preferably an organic solvent-based agent, and the content of the organic solvent in the main component is preferably 7 to 20% by mass relative to 100% by mass of the main component. The curing agent is preferably an organic solvent-based agent, and the content of the organic solvent in the curing agent is preferably 1 to 10% by mass relative to 100% by mass of the curing agent.
[0157] [Method for preparing a primer composition] The aforementioned primer composition, main component, and curing agent can be prepared by mixing (kneading) the respective raw materials to be incorporated therein. During this mixing (kneading), the raw materials may be added and mixed all at once, or they may be added and mixed in multiple stages. If the primer composition is a multi-component composition, it can be prepared by mixing (kneading) the main component and the curing agent, etc. During the mixing (kneading) process, conventionally known devices such as mixers, dispersers, and agitators can be used. Examples of such devices include dispersers, mixing / dispersing mills, mortar mixers, rolls, paint shakers, and homogenizers. Furthermore, the mixing (kneading) process may be carried out with heating, cooling, etc., depending on the season, environment, etc.
[0158] <Method for manufacturing this laminate> This laminate is typically formed on a substrate, with the substrate, primer layer, and non-skid layer being formed in that order on the substrate.
[0159] The material of the base material is not particularly limited and includes, for example, iron and steel (iron, steel, ferroalloy, carbon steel, mild steel, alloy steel, etc.), non-ferrous metals (zinc, aluminum, copper, brass, galvanized, zinc sprayed, etc.), and stainless steel (SUS304, SUS410, etc.), with iron and steel or stainless steel being preferred. The aforementioned base material is preferably a ship, a bridge, or other structure, more preferably a (large) steel or stainless steel structure such as a ship, bridge, offshore structure, plant, tank, or container, even more preferably a ship's vehicle deck or flight deck, and particularly preferably a ship's deck.
[0160] The substrate may be treated as necessary to remove rust, oil, moisture, dust, slime, and salt, and to improve the adhesion of the formed primer layer (for example, cleaning, blasting (ISO8501-1 Sa2 1 / 2), power tooling (ISO8501-1 St3, St2), friction method, and degreasing to remove oil and dust). When using, for example, mild steel (SS400, etc.) as the substrate, it is desirable to prepare the substrate surface by polishing it with grit blasting or the like (e.g., adjusting the maximum height roughness (Rz) to be around 30-80 μm) as necessary.
[0161] There are no particular limitations on the method for forming the laminate on the substrate, but preferred examples include a method comprising the following steps 1 and 2. Step 1: A step of applying the primer composition to the substrate to form a primer layer. Step 2: A step of applying the composition onto the primer layer formed in Step 1 to form a non-skid layer.
[0162] Examples of painting methods in step 1 include brush painting, air spray painting, airless spray painting, and roller painting. Spray painting is preferred because it offers excellent workability and productivity, and allows for easy painting of large areas of substrates. When applying this coating, it is preferable to apply the coating in such a way that a primer layer of the aforementioned thickness is formed. When forming the primer layer of the aforementioned thickness, it may be formed in a single coat of paint, or it may be formed in two or more coats of paint (two or more applications).
[0163] The conditions for forming the primer layer are not particularly limited and may be set appropriately depending on the method of forming the primer layer, the type of substrate, the application, the painting environment, etc. One method for forming a primer layer from a painted primer composition is to dry (cur) the primer composition. The drying (curing) temperature is usually 5 to 40°C when drying (curing) at room temperature, and usually 30°C or higher and less than 100°C, more preferably 40 to 80°C, when forced drying (curing) is performed using a hot air dryer or the like. The drying (curing) time varies depending on the drying (curing) method. For room temperature drying, it takes approximately 1 to 14 days, while for forced drying, it takes approximately 1 hour to 3 days.
[0164] Examples of painting methods in step 2 include painting using a brush, roller, or texture gun. When applying this coating, it is preferable to apply the coating in such a way that a non-skid layer of the aforementioned thickness is formed. When forming the non-skid layer of the aforementioned thickness, it may be formed in a single coat of paint, or it may be formed in two or more coats of paint (two or more applications).
[0165] The conditions for forming the non-skid layer are not particularly limited and may be set appropriately depending on the method of forming the non-skid layer, the type of substrate, the application, the painting environment, etc. One method for forming a non-skid layer from the painted composition is to dry (cur) the composition. The drying (curing) temperature and time are the same as those described in the section on the non-skid layer. [Examples]
[0166] The present invention will be described in more detail with reference to examples, but the present invention is not limited thereto.
[0167] [Examples 1-13 and Comparative Examples 1-6] The first component was prepared by mixing the raw materials listed in the "First Component" column of Table 1 or 2 below in the amounts (numerical value, parts by mass) shown in Table 1 or 2 below. Furthermore, the second component was prepared by mixing the raw materials listed in the "Second Component" column of Table 1 or 2 below in the amounts (numerical values, parts by mass) shown in Table 1 or 2 below. The first and second components prepared were mixed using a high-speed disperser in the mixing mass ratio shown in Table 1 or 2 to prepare a non-skid composition. Table 3 provides explanations of each component listed in Tables 1 and 2.
[0168] <Abrasion Resistance> Each of the prepared non-skid compositions was applied to a 150mm x 150mm x 1.0mm (thickness) cold-rolled steel sheet at a rate of 3,000g / m² relative to the surface area of the steel sheet. 2 A non-skid steel sheet was produced by painting it using a napless roller, drying it at 23°C for 15 days, and forming a non-skid layer.
[0169] A Taber-type abrasion tester manufactured by Toyo Seiki Co., Ltd. was used, in accordance with JIS K 5600-5-9:1999 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 9: Abrasion resistance (abrasion wheel method)". A steel plate with a non-skid layer was fixed to a rotating table positioned horizontally (perpendicular to gravity) in the testing machine. A pair of wear wheels (H-22 type) were placed on the non-skid layer so that each wear wheel was subjected to a load of 500g, and the rotating table was rotated 100 times. The mass of the steel plate with a non-skid layer was measured using a high-precision balance before and after the wear test, and the mass loss was determined. The results are shown in Table 1 or 2. In this invention, it is stated that the wear resistance is excellent when the mass loss is 0.6% by mass or less.
[0170] [Table 1]
[0171] [Table 2]
[0172] [Table 3]
[0173] [Preparation examples P1 to P7] The main ingredient was prepared by mixing the raw materials listed in the "Main Ingredient" column of Table 4 below in the amounts (numerical value, parts by mass) shown in Table 4 below. Furthermore, the hardening agent was prepared by mixing the raw materials listed in the hardening agent column of Table 4 below in the amounts (numerical value, parts by mass) shown in Table 4 below. The prepared main component and curing agent were mixed using a high-speed disperser in the mixing mass ratio shown in Table 4 to prepare a primer composition. Table 5 provides a description of each component listed in Table 4.
[0174] [Table 4]
[0175] [Table 5]
[0176] [Examples L1-14 and Comparative Examples L1-7] A primer layer was formed on a 150mm x 150mm x 6.0mm (thickness) shot-blasted steel plate (Rz: 80μm) by air spraying each of the primer compositions listed in Table 6 or 7, so that the resulting dry film thickness would be 150μm, and then drying at 23°C for one day. On the formed primer layer, apply each of the non-skid compositions listed in Table 6 or 7 at a rate of 3,000 g / m². 2 A non-skid laminated steel sheet was fabricated by painting it using a napless roller, drying it at 23°C for 15 days to form a non-skid layer.
[0177] <Coefficient of static friction> The fabricated steel plate with a non-skid laminate was placed on a horizontal (perpendicular to gravity) platform with the steel plate facing downwards. Water was sprayed onto the non-skid layer of the steel plate with the non-skid laminate using a spray bottle to moisten the non-skid layer. A neoprene rubber sheet (hardness 80 degrees) measuring 15 cm x 15 cm x 1 cm thick was placed on top of the moistened non-skid layer, and a cubic iron block measuring 13 cm on each side and weighing 18 kg was placed on top of the sheet. Subsequently, the cubic block was pulled horizontally relative to the platform using an IMADA FB-500N mechanical force gauge, and the force (in Newtons) required to move the cubic block was measured. This test was repeated three times, and the average force required to start the cube block moving across the three tests was defined as F(N). The coefficient of static friction (μ) was then calculated using the following formula (5). The results are shown in Table 6 or 7. μ = F / 180 ... (5)
[0178] <Impact Resistance> A GARDCO impact testing machine compliant with ASTM G 14 (Impact resistance of pipeline coatings) was used. The base was changed to a 40mm thick base that could fix the steel plate with non-skid laminate so that it would not move when the tap was dropped, and could be aligned to the predetermined impact position.
[0179] The fabricated steel plate with a non-skid laminate was placed on the base of the impact testing machine, and a tap (weighing 1.8 kg, tip shape: 5 / 8 inch hemispherical) was dropped onto the non-skid layer of the steel plate with the non-skid laminate from a height of 1.2 m above the non-skid layer. This process of dropping the taps onto the non-skid layer was performed 25 times. The taps were dropped onto the non-skid layer in the order shown in Figure 1, near the center of each cell when the central part of the non-skid layer surface is divided into 25 sections in a plan view (hereinafter, the locations where the taps were dropped onto the non-skid layer will be referred to as "impact points").
[0180] The total area of the 25 cells shown in Figure 1 is approximately 58 cm². 2The distance between the point of impact when the tap was dropped into a certain cell and the point of impact when the tap was dropped into an adjacent cell that shares one side with the same cell was set to 20 ± 1.5 mm. After dropping a tap into the non-skid layer 25 times, the force required to peel off the non-skid laminate from the steel sheet with a sharpened steel chisel was determined, specifically at locations other than the 25 cells, and at least 25 mm away from the 25 cells.
[0181] Next, using a force less than the force previously confirmed, the non-skid laminate at the impact points and the areas between impact points was peeled off the steel plate, and the peeled non-skid laminate was removed from the steel plate. In the above tests, there were a total of 40 pairs of adjacent impact points separated by 20 ± 1.5 mm. If these adjacent impact points were connected by removing the delaminated non-skid laminate, a score of -2.5 points was deducted for each connected point (a score of 100 was given if none of the 40 pairs of adjacent impact points were connected (i.e., the non-skid laminate was present between the adjacent impact points)). These evaluation scores are shown in Table 6 or 7. In this invention, a product is considered to have excellent impact resistance if its evaluation score is 95 points or higher, that is, if it has two or fewer connected points.
[0182] [Table 6]
[0183] [Table 7]
Claims
1. A non-skid composition, The non-skid composition comprises a first agent containing an epoxy resin (AN) and a second agent containing an amine compound (BN). The epoxy equivalent of the solid content of the total epoxy compound contained in the first agent is 450 or less. The amine compound (BN) includes an alicyclic amine compound. The volume concentration of particulate solids (PVC N) in the non-skid composition is 40.0% or more. A non-skid composition for forming a non-skid layer having a surface static friction coefficient of 0.80 or higher.
2. It contains aggregate with an average particle size of 0.1 to 3.0 mm. The aggregate content is 15% by mass or more relative to 100% by mass of the solid content of the first agent. The non-skid composition according to claim 1.
3. The non-skid composition according to claim 2, wherein the aggregate comprises at least one selected from aluminum oxide and aluminum powder.
4. A non-skid layer formed from the non-skid composition according to any one of claims 1 to 3.
5. A non-skid laminate having a primer layer and a non-skid layer according to claim 4.
6. Volume concentration of particulate solids in the primer layer (PVC P The non-skid laminate according to claim 5, wherein the percentage of ) is 32.0% or less.
7. The aforementioned PVC P and the volume concentration of particulate solids in the non-skid layer (PVC N ) is the difference between PVC N - PVC P The non-skid laminate according to claim 6, wherein the content is 19.0% or more.
8. The non-skid laminate according to claim 5, wherein the primer layer is a layer formed from a primer composition containing a main component comprising an epoxy resin (AP) and a curing agent comprising an amine compound (BP).
9. The non-skid laminate according to claim 8, wherein the primer layer and the non-skid layer are in contact.
10. A non-skid laminate according to claim 5, for use in ships.
Citation Information
Patent Citations
Floating colored sand self-leveling floor coating and preparation method thereof
CN107586504A
Colddcuring epoxy resin coating material composition and its preparation
JP1981038317A
Two-component epoxy resin coating system
JP2000178502A
Lightweight, low-heavy-metal content, two-component anti-slip epoxy coating for decks or floors.
JP2010515787A
Non-slip composition
KR1020200097898A